Impact of increased printing speed on component properties and bonding characteristics of selective laser sintered PA 2200 parts. (30th May 2023) - Poignee, Leon; Barmouz, Mohsen; Bösinger, Robert; Azarhoushang, Bahman
The impact of increased sintering rate on the dimensional accuracy, surface topology, and tensile properties of selective laser-sintered polyamide (PA 2200) flat samples was investigated. The sintering rate is significantly influenced by the scan speed and the scan spacing. It was observed that different dimensional accuracies were achieved depending on the measurement direction. The surface topology changed depending on which of the two parameters was increased. Besides, it could be observed that an increase in the sintering rate did not result in a change in yield and tensile strength but in a decrease of 37% in elongation at break. Post-treated samples using different grinding processes were bonded and subjected to a tensile test. It was found that increasing the surface roughness up to an optimum value improved the tensile strength of the bonded joint. Furthermore, surface activation enhanced the tensile strength of the joint by up to 28%.